Temperature evolution of lattice misfit in Hf and Mo variations of the Al10Co25Cr8Fe15Ni36Ti6 compositionally complex alloy. (November 2020) - Manzoni, A.M.; Haas, S.; Kropf, H.; Duarte, J.; Cakir, C.T.; Dubois, F.; Többens, D.; Glatzel, U.
Abstract: Misfits of γ-γ' based Al10 Co25 Cr8 Fe15 Ni36 Ti6 and its Mo- and Hf-variations are studied up to a temperature of 980 °C and compared with Ni- and Co-based superalloys. The trace elements decrease (Hf) or increase (Mo) the edge radii of the γ' cuboids without changing their sizes. Atom probe measurements revealed that the Hf alloy prefers the γ' phase while Mo prefers the γ matrix, leading to a lattice parameters enhancement of both phases, as could be revealed by synchrotron X-ray diffraction. The misfit is influenced in opposite ways: Hf increases the positive misfit, while Mo reduces it at all investigated temperatures. Graphical abstract: Image, graphical abstract